Angelina : an unauthorized biography - Morton, Andrew, 1953- (New York : St. Martin's Press, 2010)
At first glance, Angelina Jolie might seem to be someone without any secrets, talking openly about her love life, drug use, etc. Yet mysteries remain: What went on in her brief, impulsive marriages to Jonny Lee Miller and Billy Bob Thornton, and what is going on with Brad Pitt? What's behind the feud with her father, actor Jon Voight? What drove her to become a mother of six children in six years? And how did this talented but troubled young actress, barely 35 years old, become the "most powerful celebrity in the world" (unseating Oprah Winfrey) on Forbes' 2009 Celebrity 100 list, working with victims of poverty and disaster? Andrew Morton draws upon original interviews and research to show us what shaped her as a child, as an actress, and as a woman struggling to overcome personal demons never before revealed.--From publisher description
Includes index
Keywords: Jolie, Angelina, -- 1975-; Motion picture actors and actresses -- United States -- Biography